Feng shui for dummies - Kennedy, David (David Daniel). (Hoboken, N.J. : Wiley, 2011)
Discover how to apply feng shui principles to the home and workplace, in order to achieve a better life.
Includes bibliographical references and index.
Keywords: Feng shui